2020
DOI: 10.1002/essoar.10503172.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Properties of Plasma Waves Observed Upstream from Mars

Abstract: We describe a new method to analyze the properties of plasma waves and apply it to observations made upstream from Mars by the Mars Atmosphere and Volatile EvolutioN (MAVEN) mission. The slow measurement cadence of most charged particle instrumentation has limited the application of analysis techniques based on correlations between particle and magnetic field measurements. We show that we can extend the frequency range of applicability for these techniques, for a subset of waves that remain nearly coherent ove… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 53 publications
3
7
0
Order By: Relevance
“…This is consistently seen for all HR groups and the entire span of available MAVEN data, confirming the results from Halekas et al. (2020) between September and November 2018. Although this trend disagrees with linear wave growth theory (Gary et al., 1986), Delva et al.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is consistently seen for all HR groups and the entire span of available MAVEN data, confirming the results from Halekas et al. (2020) between September and November 2018. Although this trend disagrees with linear wave growth theory (Gary et al., 1986), Delva et al.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, MGS did not possess an onboard SW ion detection instrument to study SW properties during PCW events. As MAVEN provides both magnetic field and SW measurements, this mission presents an excellent opportunity to perform studies focused on these low frequency plasma waves (e.g., Andrés et al., 2020; Halekas et al., 2020; Liu et al., 2020). In this work, we present an extensive study with MAVEN observations covering almost 3 Martian years, identifying PCW events with strict criteria, to analyze the occurrence rate variability, main wave properties, and SW conditions that favor their presence.…”
Section: Introductionmentioning
confidence: 99%
“…A number of lines of evidence, including scattered Lyman‐α (Bhattacharyya et al., 2015; Chaffin et al., 2014; Clarke et al., 2014), hydrogen pickup ions (Rahmati et al., 2018; Yamauchi et al., 2015), low frequency plasma waves driven by hydrogen pickup ions (Bertucci et al., 2013; Halekas et al., 2020; Romanelli et al., 2016; Romeo et al., 2021), and byproducts of charge exchange between solar wind protons and neutral hydrogen (Halekas, 2017) have demonstrated that the Martian hydrogen corona has a strong seasonal variability, peaking shortly after perihelion in the southern summer season. This seasonal variability apparently results from the Martian dust storm cycle, which enables transport of water to higher altitudes, where it undergoes destructive reactions that produce hydrogen that can then escape thermally (Chaffin et al., 2017; Fedorova et al., 2020; Stone et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These cyclotron waves have well‐defined frequencies at fci=qB2πmi ${f}_{ci}=\frac{qB}{2\pi {m}_{i}}$, where q is the charge of an electron, B is the magnetic field, and m i is the mass of the ion species i . We note that in this study, the term ICW, when at the proton gyrofrequency, is not the same as proton cyclotron waves, which are related to newborn pickup protons (e.g., Halekas et al., 2020; Romanelli et al., 2016; Romeo et al., 2020; Ruhunusiri et al., 2016). B is observable using the Mars Atmosphere and Volatile EvolutioN (MAVEN) mission magnetometer (MAG) (Connerney et al., 2015; Jakosky, Grebowsky, et al., 2015; Jakosky, Lin, et al., 2015).…”
Section: Introductionmentioning
confidence: 70%